GENETIC DIVERSITY OF ASH GOURD (Benincasa hispida) GENOTYPES (Bangladesh Journal of Plant Breeding and Genetics, 2015)
An experiment was conducted to study the field performance, variability and genetic divergence for yield and yield contributing characters of 46 ash gourd genotypes at the Horticulture Farm, Bangladesh Agricultural University, Mymensingh. Wide range of variations were found among the ash gourd genotypes in respect of different parameters such as vine length at harvest, fruit length, fruit diameter, sex ratio, number of fruits plant-1, average weight fruit-1 and yield plant-1. The genotype BH21 showed the highest performance in number of fruits plant-1 and yield plant-1. In respect of average weight fruit-1, the genotype BH16 produced the heaviest (1.86 kg) fruit and the genotype BHl7 produced the lightest (0.67 kg) fruit. The genotype BH18 had the highest sex ratio (8.16) and the genotype BH14 had the lowest sex ratio (3.44). In case of number of fruits plant-1, the genotype BH46 and BH53 had the minimum number of fruits (1.33) and the genotype BH21 had the maximum number of fruits (16.16) per plant which was statistically similar with the genotype BH12 (15.00). The genotypes were also tested for genetic divergence utilizing the multivariate analysis. The genotypes were grouped into eight clusters. However, there was no relationship found between genetic divergence and geographic distribution of the genotypes.